2001
DOI: 10.1046/j.1365-2796.2001.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibrinogen level and long‐term prognosis in Norwegian middle‐aged patients with previous myocardial infarction. A 10 year follow‐up study

Abstract: Abstract. Retterstol L, Kierulf P, Pedersen JC, Bohn M, Bakken A, Erikssen J, Berg K (Institute of Medical Genetics, University of Oslo and Ulleva Êl University Hospital, Oslo; and Central Hospital of Akershus, Nordbyhagen, Norway). Plasma ®brinogen level and long-term prognosis in Norwegian middle-aged patients with previous myocardial infarction. A 10 years follow-up study. J Intern Med 2001; 249: 511±518.Objectives. To investigate the prognostic value of plasma ®brinogen level amongst middle-aged survivors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In addition, those in the top quartile of fibrinogen levels have a 2 times greater risk of cardiac death. 15,16 D-Dimer was found in our study to be similarly predictive for primary cardiac events in both hypertensive and nonhypertensive patients after infarction. This observation indicates that an enhanced thrombogenic activity contributes to cardiac events in both groups of patients.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, those in the top quartile of fibrinogen levels have a 2 times greater risk of cardiac death. 15,16 D-Dimer was found in our study to be similarly predictive for primary cardiac events in both hypertensive and nonhypertensive patients after infarction. This observation indicates that an enhanced thrombogenic activity contributes to cardiac events in both groups of patients.…”
Section: Discussionsupporting
confidence: 67%
“…13,[15][16][17][18][19] However, fibrinogen failed to enter our final predictive model. This could be because the levels of fibrinogen in our patients were not as high as in other studies in which there was a significant association with cardiac events.…”
Section: Discussionmentioning
confidence: 93%
“…Studies of patients with MI or unstable heart disease have reported associations between various inflammatory markers, eg, fibrinogen, CRP, serum amyloid A, interleukin-6, and an adverse prognosis. [7][8][9][10] Inflammation in unstable coronary plaque and the effects of the myocardial ischemia on the degree of inflammation could contribute to these relationships. Elevated ISPs, measured many years before the coronary events, were associated with a higher proportion of CHD deaths in the present study.…”
Section: Engström Et Al Isps and Fatality After Future Coronary Eventmentioning
confidence: 99%
“…[7][8][9][10] However, as many CHD deaths occur outside hospital, the inclusion of out-of-hospital deaths is an important prerequisite for a representative study of survival after acute coronary events. 1 Previous studies from the population-based cohort "Malmö Preventive Study" have shown that the incidence of MI and stroke is increased in men with elevated plasma levels of fibrinogen, orosomucoid (␣ 1 -acid glucoprotein), ␣ 1 -antitrypsin, haptoglobin, or ceruloplasmin, ie, 5 ISPs.…”
mentioning
confidence: 99%
“…The association found between a high fibrinogen level and an increased risk of mortality confirms results from previous studies. Increased fibrinogen levels have been found to be a risk factor for CAD [47] and have also been shown to be a predictor of cardiac death in patients with previous AMI [48]. A high SR was also associated with an increased hazard ratio in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%